Nailfold capillary patterns in healthy subjects: A real issue in capillaroscopy - Ingegnoli, Francesca; Gualtierotti, Roberta; Lubatti, Chiara; Bertolazzi, Chiara; Gutierrez, Marwin; Boracchi, Patrizia; Fornili, Marco; De Angelis, Rossella (Microvascular research, 2013)
Nailfold capillaroscopy has been extensively applied in a broad spectrum of pathologic conditions, but very few data have been published in healthy individuals. The aim of this study was to describe the nailfold capillary findings on a large series of healthy subjects using the video-capillaroscopy technique. Nailfold capillaries were studied based on their morphology, dimensions and density. Then, to evaluate jointly the association between different capillary findings in groups of subjects which were homogeneous for their characteristics, cluster analysis was performed. The results (median) of capillary measurements were as follows: loop length 207μm, external diameter 39μm, internal diameter 17μm, apical diameter 17μm, and intercapillary distance 143μm. Based on the cluster analysis three major “normal” morphologic capillaroscopic patterns were depicted: 1) the “normal” pattern mainly with 2 to 5 U-shaped loops/mm and ≤2 tortuous loops/mm; 2) the “perfect normal” pattern with ≥5 U-shaped loops/mm and 3) the “unusual normal” with at least 1 meandering or bushy loop, or at least 1 microhemorrhage, or with >4 crossed loops/mm. Regarding the loop measurements, the majority of subjects had a median of 7capillaries/mm with a median length of 198μm. •Very few data have been published about capillaroscopy in healthy individuals.•We aimed to depict the nailfold microcirculation on a large series of subjects.•Nailfold capillaries were studied based on their morphology, dimensions and density.•Our findings may be considered part of the normal capillaroscopic pattern.•Knowledge of the normal range allows a better identification of a microangiopathy.